Techno-economic and carbon emissions analysis of biogas utilisation systems in the UK - Lamond, Alexander Robert (2018)
Biogas is a renewable and carbon neutral fuel, that can help the UK meet its increasing energy demand, while simultaneously reducing the net greenhouse gas emissions. All the biogas utilisation routes modelled, return positive avoided greenhouse gas (GHG) emissions. Biogas to combined heat and power (CHP) returns higher avoided emissions than biogas upgrading to biomethane and injection into the gas grid across the entire heat utilisation range (0% to 100%). The current renewable energy incentives, offered by the UK government, allow utilising biogas via either CHP, or biomethane production to return positive net present values (NPV).